Rūḥ-i naẓm : Urdū shāʻirī kā bihtarīn intiḵẖāb aur Urdū shuʻarā par ek ijmālī tabṣirah - Tājvar Najībābādī; Vafā, Melā Rām (SAMP early 20th-century Indian books project, 1938)
Collection of selected Urdu poetry; includes editorial introduction.